Notion and Types of Information Offenses in Social Networks - Сафончик, Оксана Іванівна; Сафончик, О. І.; Сафончик, Оксана Ивановна; Safonchyk, Oksana I.; Safonchyk, Oksana; Глиняна, Катерина Михайлівна; Глиняна, К. М.; Глиняная, Екатерина Михайловна; Hlyniana, Kateryna M.; Hlyniana, Kateryna; Бехруз, Хашматулла Набієвич; Бехруз, Х. Н.; et al. (Mattingley Publishing, 2020)
The research paper deals with the problems of determining the nature of information offenses in social networks. Besides, the authors provide definitions of information offenses, outline the types of such offenses, and also propose a vision of ways to improve legislation in the relevant field. Among information offenses there outlined dissemination of illegal collection and use of information, unauthorized access to information resources and social networks, illegal copying of information in electronic systems, theft of information from libraries, archives, banks and databases, breach of information processing technologies, launch of virus programs, Trojans, phishing programs, destruction and modification of data in information systems, interception of information in technical channels of its leakage, manipulation of public and individual consciousness, etc. The article identifies the decisive role of the state in providing protection against information offenses. Thus, he state forms an official information policy, organizes the work of relevant bodies, supports the activities of public organizations, controls the development and production of information security means, as well as conducts practical activities to protect the internal market from penetration of low-quality information products.

Дослідницька робота присвячена проблемам визначення характеру інформаційних правопорушень у соціальних мережах. Крім того, автори надають визначення інформаційних правопорушень, окреслюють види таких правопорушень, а також пропонують бачення шляхів вдосконалення законодавства у відповідній галузі. Серед інформаційних правопорушень виділено розповсюдження, незаконний збір та використання інформації, несанкціонований доступ до інформаційних ресурсів та соціальних мереж, незаконне копіювання інформації в електронних системах, крадіжки інформації з бібліотек, архівів, банків та баз даних, порушення технологій обробки інформації, запуск вірусних програм, троянських програм, фішинг-програм, знищення та модифікація даних в інформаційних системах, перехоплення інформації в технічних каналах її витоку, маніпуляції суспільною та індивідуальною свідомістю тощо. У статті визначено вирішальну роль держави у забезпеченні захисту від інформаційних правопорушень. Таким чином, вона формує офіційну інформаційну політику, організовує роботу відповідних органів, підтримує діяльність громадських організацій, контролює розробку та виробництво засобів захисту інформації, а також проводить практичні заходи щодо захисту внутрішнього ринку від проникнення інформаційної продукції низької якості.

Исследовательская работа посвящена проблемам определения характера информационных правонарушений в социальных сетях. Кроме того, авторы предоставляют определение информационных правонарушений, определяют виды таких правонарушений, а также предлагают видение путей совершенствования законодательства в соответствующей отрасли. Среди информационных правонарушений выделено распространение, незаконный сбор и использование информации, несанкционированный доступ к информационным ресурсам и социальным сетям, незаконное копирование информации в электронных системах, кражи информации из библиотек, архивов, банков и баз данных, нарушение технологий обработки информации, запуск вирусных программ, троянских программ , фишинг-программ, уничтожение и модификация данных в информационных системах, перехват информации в технических каналах ее утечки, манипуляции общественным и индивидуальным сознанием и тому подобное. В статье определено решающую роль государства в обеспечении защиты от информационных правонарушений. Таким образом, оно формирует официальную информационную политику, организует работу соответствующих органов, поддерживает деятельность общественных организаций, контролирует разработку и производство средств защиты информации, а также проводит практические меры по защите внутреннего рынка от проникновения информационной продукции низкого качества.
Safonchyk O. Notion and Types of Information Offenses in Social Networks / O. Safonchyk, K. Hlyniana, B. Khashmatulla // Test Engineering and Management. – V. 83. - Mattingley Publishing, 2020. – P. 6880-6887.
Keywords: civil information torts; information crimes; information offenses; information sphere; information technologies; legal mechanism; social networks; цивільні інформаційні делікти; інформаційні злочини; інформаційні правопорушення; інформаційна сфера; інформаційні технології; правовий механізм; соціальні мережі; гражданские информационные деликты; информационные преступления; информационные правонарушения; информационная сфера; информационные технологии; правовой механизм; социальные сети; Research Subject Categories::LAW/JURISPRUDENCE